Enhancing Arabic Writing Skills Through Realistic Images at MI Hiyatul Ilmi - Aulia Zachra Lestar; Siskha Putri Sayekti (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This study was motivated by the low Arabic writing proficiency among students at Madrasah Ibtidaiyah. Observations during the teaching and learning process revealed that the teacher relied solely on student worksheets (LKS) without incorporating appropriate instructional media. This lack of media use was considered a contributing factor to students’ limited writing skills. The objectives of this study are twofold: first, to analyze the effectiveness of reality-based learning media in assessing students’ Arabic writing skills; and second, to observe improvements in these skills following the implementation of reality image media in Arabic language instruction. This research employed Classroom Action Research (CAR) as the methodological approach. The study involved 22 students, comprising 14 boys and 8 girls. The research was conducted over two cycles, each involving planning, action, observation, and reflection stages. The findings indicate that the use of reality image media significantly enhanced students’ Arabic writing skills. In the first cycle, the writing performance reached only 31.8%. However, after refining the approach in the second cycle, the achievement rose to 86.3%. The students’ average score on the Arabic writing test reached 88.6, which exceeds the Minimum Mastery Criterion (KKM) set at 75. These results suggest that reality-based media can serve as an effective tool to support the development of Arabic writing proficiency at the elementary school level.